2017
DOI: 10.18061/1811/81047
|View full text |Cite
|
Sign up to set email alerts
|

Farm Crime in England and Wales: A Preliminary Scoping Study Examining Farmer Attitudes

Abstract: Farms stand apart from other rural businesses in the levels of crimes they experience, and the impact of farm crime reverberates far beyond the immediate rural community. However, there continues to be a lack of interest in farm crime as a research topic in both England and Wales. This study explores attitudes of farmers towards farm crime, crime prevention, the police, and potential predictors of farm victimisation 2 . An online survey was completed by 71 farmers; a further 55 farmers partially completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Previous farm crime surveys, across a number of different countries, have found relatively high rates of past-year victimisation. These have ranged from: 30% in a Swedish study (Ceccato 2016 ); 50 and 62% in an American study (Mears et al 2007 ); 50 (Morris et al 2020 ), 62 (Smith and Byrne 2017 ) and 82.5% (Sugden 1999 ) in three British studies; and 87% in an Australian study (Barclay and Donnermeyer 2002 ). Another American study found that 33.4% of farms had been the victim of theft (McIntyre et al 2017 ).…”
Section: Review Of Farm Victimisations Studiesmentioning
confidence: 96%
“…Previous farm crime surveys, across a number of different countries, have found relatively high rates of past-year victimisation. These have ranged from: 30% in a Swedish study (Ceccato 2016 ); 50 and 62% in an American study (Mears et al 2007 ); 50 (Morris et al 2020 ), 62 (Smith and Byrne 2017 ) and 82.5% (Sugden 1999 ) in three British studies; and 87% in an Australian study (Barclay and Donnermeyer 2002 ). Another American study found that 33.4% of farms had been the victim of theft (McIntyre et al 2017 ).…”
Section: Review Of Farm Victimisations Studiesmentioning
confidence: 96%
“…This was the approach adopted by Smith (2017) where data from farmers who had been a victim of farm crime was obtained, as well as responses from those farmers who had not victims.…”
Section: Sampling Considerations and External Validitymentioning
confidence: 99%
“…Despite this, it is only in recent times that online surveys have been used to explore issues around rural crime. In the United Kingdom currently, there have been very few examples of academic research employing this methodology and only, seemingly, within the last 5 years (Morris & Norris, 2020; Morris et al, 2017; Smith, 2017, 2020). Rural stakeholders continue to dominate the use of online surveys to explore rural crime (Farmers Weekly, 2019; National Rural Crime Network, 2018; NFU Cymru, 2021; NFU Mutual, 2020).…”
Section: Rural Online Surveys: a Brief Historymentioning
confidence: 99%
See 2 more Smart Citations